Effect of changes in tax/benefit policies in Austria 1998 - 2005 - Michael Fuchs; Christine Lietz (University of Essex, Institute for Social and Economic Research (ISER), 2007)
The aim of this paper is to evaluate whether policy reforms in Austria between 1998 and 2005 were successful in meeting redistributive objectives and in reducing poverty. For the analysis we use the tax/benefit micro-simulation model EUROMOD. Due to the sequence of reforms and the use of two datasets, the period under review is split into two parts: 1998 to 2003 and 2003 to 2005. Important changes in the first period were the tax reform 2000, the introduction of the universal childcare benefit (“Kinderbetreuungsgeld”) as well as increases in family-targeted benefits and tax reliefs. We find that the policy reforms were in general clearly progressive and family-friendly. However, as with elderly people, the situation did not improve for all population groups at risk of poverty. In the period from 2003 to 2005 the tax reform 2004/05 was introduced and contributions to health insurance were raised. We find that the measures had no significant impact on poverty and income distribution; however, in total they increased the disposable income for almost all population groups. The analysis is completed by the assessment of the redistributive impact of two hypothetical policy changes in favour of lower income groups, namely the continuous introduction of employees' social security contributions above the lower threshold for contributions (“Geringfügigkeitsgrenze”) and the yearly indexation of family benefits.
Keywords: C8; D31; I3; 330; Austria; policy reform; inequality; redistribution; micro-simulation; Sozialreform; Wirkungsanalyse; Einkommensverteilung; Armut; Soziale Lage; Gesellschaft; Simulation; Österreich